2022
DOI: 10.1002/cyto.a.24688
|View full text |Cite
|
Sign up to set email alerts
|

Impact of red blood cell lysing on rare event analysis

Abstract: The challenges associated with analyzing rare cells are dependent on a series of factors, which usually require large numbers of cells per sample for successful resolution. Among these is determining the minimum number of total events needed to be acquired as defined by the expected frequency of the target cell population. The choice of markers that identify the target population, as well as the event rate and the number of aborted events/second, will also determine the statistically significant detection of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Applying bulk lysis protocols results in a significant decrease in non‐necrotic cells (Figure 2, lower row; and Supplementary Table 2) compared to MSP protocols. This decrease may be associated with the detrimental effects produced by erythrocyte lysis solutions containing ammonium chloride and washing steps [13–16]. Regarding target cell frequency detection, we observed a significant loss of EGFP‐K562 cells when preparing samples with BL methods for all established percentages (Figures 1 and 2, upper row; and Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Applying bulk lysis protocols results in a significant decrease in non‐necrotic cells (Figure 2, lower row; and Supplementary Table 2) compared to MSP protocols. This decrease may be associated with the detrimental effects produced by erythrocyte lysis solutions containing ammonium chloride and washing steps [13–16]. Regarding target cell frequency detection, we observed a significant loss of EGFP‐K562 cells when preparing samples with BL methods for all established percentages (Figures 1 and 2, upper row; and Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 87%
“…That alteration resulted in under‐ and over‐estimation of those target cells when calculating their frequency relative to total leukocytes [15]. Another study of our group reported that erythrocyte lysing solutions can cause an over‐ or under‐estimation of rare cells in MRD models and in chronic lymphocytic leukemia [16].…”
Section: Discussionmentioning
confidence: 99%
“…Rico et al., reported that red cell lysis solutions can reduce the cell viability and negatively affect the epitopes. 13 (Step 19).…”
Section: Troubleshootingmentioning
confidence: 99%